Mediating Effect of Earnings Management on Financial Performance: The Importance of Good Corporate Governance - Fahmi Rizani; Akhmad Yafiz Syam; L. Lisandri (Australasian Accounting, Business and Finance Journal, 2022)
Purpose: This study investigates the effect of corporate governance on financial performance by taking into account the mediating effect of earnings management. Design: By using a structural equation modeling and partial least squares approach and a sample of listed banks in Indonesia observed between 2010 and 2015, this research proves that good corporate governance has a significant effect on earnings management and, in turn, that earnings management has an adverse impact on a company’s financial performance. Findings: An increase in managerial and institutional ownership leads to a decrease in earnings management, which can improve a company’s financial performance. Originality: This research shows that by applying good corporate governance mechanisms, a company can avoid agency conflicts, minimize earnings manipulation by managers, and obtain reliable company performance valuations.
Keywords: corporate governance; corporate financial performance; earnings management; institutional ownership; managerial ownership; Indonesia